1985
DOI: 10.1007/bf00440960
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial meningioma with abnormal localization of bone-seeking radiopharmaceutical: Correlation with gross and microscopic pathology

Abstract: Meningioma is one of the neoplasms in which there may be extraosseous localization of bone-seeking radiopharmaceuticals. Tumor calcification, calvarial erosion, and the formation of reactive bone have been proposed as the cause of this abnormal tracer localization. We present a patient with a frontal meningioma that was evaluated using 99mTc-methylene-diphosphonate bone scintigraphy, head computed tomography, and skull radiography; the homogeneous density seen in the radiographic studies corresponded to the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…71 As an example, 99m Tc-MDP detected calcifications in meningiomas arise from calvarial erosion, the formation of reactive bones, and tumor-induced calcification. 72 The latter is postulated to arise from low levels of intracellular adenosine triphosphate, leading to metabolic impairment and weakening of cell membrane, and followed by accumulation of calcium in the mitochondria. Presumably this intracellular nucleation provides a template for the uptake of radiotracers reminiscent of BP absorption onto the HA crystal of osseous tissue, whose nucleation is mediated in part by phosphorylated membrane components during normal matrix mineralization.…”
Section: Bisphosphonates In the Diagnosis Of Bone Diseasesmentioning
confidence: 99%
“…71 As an example, 99m Tc-MDP detected calcifications in meningiomas arise from calvarial erosion, the formation of reactive bones, and tumor-induced calcification. 72 The latter is postulated to arise from low levels of intracellular adenosine triphosphate, leading to metabolic impairment and weakening of cell membrane, and followed by accumulation of calcium in the mitochondria. Presumably this intracellular nucleation provides a template for the uptake of radiotracers reminiscent of BP absorption onto the HA crystal of osseous tissue, whose nucleation is mediated in part by phosphorylated membrane components during normal matrix mineralization.…”
Section: Bisphosphonates In the Diagnosis Of Bone Diseasesmentioning
confidence: 99%
“…showed 2 different intensities in radiological and scintigraphical views between reactive hyperostosis and tumor calcification in their total cases of meningioma [13] . Shih et al reported a meningioma case with no calvarial erosion and reactive bone formation [14] .…”
Section: Discussionmentioning
confidence: 99%
“…The later arise from the ovaries or peritoneum, and certain criteria must be fulfilled in order to characterize a carcinoma with psammoma bodies as psammocarcinomas (22). Cases reported in the literature include primary psammocarcinomas of the ovary or peritoneum, or psammoma deposits in benign and malignant conditions such as serous adenocarcinoma of the ovaries, thyroid, meningioma, pancreas and calcifications in metastatic lesions (3,6,14,15,16,20,21,22,25,26). Our case displays the presence of psammoma bodies in metastatic lymph nodes diagnosed during ovarian cancer relapse after 18 years.…”
Section: Literature Review and Discussionmentioning
confidence: 99%